Penerapan buku teks IPA terpadu dalam pendekatan scientific terhadap hasil belajar siswa kelas VIII SMPN 13 Padang - Syafri Syafri; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2019)
Learning the nested models combined with the scientific approach can be used to integrate student learning skills and enhance learning experiences. Das Sein shows that the integration of science materials in the books used in schools is still separate, the scientific approach is incomplete, and the learning outcomes of students have not yet reached the value of the science standard. The solution to this problem is to apply the Integrated Science Text Book Based on Nested Models with Character Values Themes of the Movement of Living Creatures. This research aims to investigate the differences in student learning outcomes and the relationship of Integrated Science Textbooks in the Scientific Approach to Learning Outcomes of Class VIII Students of SMPN 13 Padang. The type of research conducted is quasi-experimental research with research design Pretest-Posttest Control Group Design. The population in this result were all class VIII students of SMPN 13 Padang who were enrolled in the 2018/2019 Academic Year. Sampling in the result was conducted by combining purposive sampling technique and cluster random sampling. The research instrument consisted of the posttest sheet, eksperiment evaluation sheet, and student attitude observation sheet. The data in this result were analyzed using descriptive analysis, two mean similarity tests, simple linear regression, and correlation tests at the 0.05 significance level for all student competencies. The results of the study concluded that there were significant differences in student learning outcomes between students using Character Value Integrated Science textbooks with students using School Books and there was a significant relationship between the application of Character Value Integrated Integrated Science Textbooks to student learning outcomes for all aspects of learning outcomes. In the similarity test the two average states there are differences in learning outcomes for all aspects of student competence. In the product moment correlation test expressed the level of moderate and very strong relationships. In the test of correlation significance there is a significant relationship. The calculation of the determination coefficient obtained the percentage contribution of Character Value Integrated IPA Text Books for attitude aspects of 16.74%, knowledge aspects of 16.893%, and skills aspects of 67.16%.